Tephrostratigraphy of Pleistocene-Holocene deposits from the Detroit Rise eastern slope (northwestern Pacific) - Derkachev, Alexander; Gorbarenko, Sergey; Portnyagin, Maxim; Zhong, Yi; Nikolaeva, Nataliya; Shi, Xuefa; Liu, Yanguang (Frontiers in Earth Science, 2023)
The main goal of the study is to establish the spatial and temporal distribution of pyroclastic material from large explosive eruptions of the volcanoes of Kamchatka, the Kuril, and Aleutian Islands to create a generalized tephrochronological model and reveal patterns of explosive activity in this region. This paper presents new data on the composition of volcanic ash (tephra) found in the Pleistocene deposits of the northwestern Pacific from the eastern slope of the Detroit Rise (northwestern part of the Imperial Ridge), 450–550 km east of the Kamchatka Peninsula. Eleven layers and lenses of tephra aged from 28 to 245 ka, which were previously unknown, were studied in the core Lv63-4-2. Their stratigraphic position and age were determined based on age models developed in this study. Based on the geochemical composition of volcanic glass (determined using an electron microprobe), seven layers were correlated with tephra from several cores in the northwestern Pacific and the Bering Sea. The obtained results supplement the information on large explosive eruptions of volcanoes in the region and their periods of activity. They also allow the development of a generalized tephrochronological model of Quaternary deposits, which is necessary for stratigraphic correlation, and of paleooceanological and paleogeographic reconstructions.